2022
DOI: 10.3390/antiox12010013
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Oxidative Stress and Kidney Health: Bridging the Gap between Animal Models and Clinical Reality

Abstract: Oxidative stress arises when the generation of reactive oxygen species or reactive nitrogen species overwhelms antioxidant systems. Developing kidneys are vulnerable to oxidative stress, resulting in adult kidney disease. Oxidative stress in fetuses and neonates can be evaluated by assessing various biomarkers. Using animal models, our knowledge of oxidative-stress-related renal programming, the molecular mechanisms underlying renal programming, and preventive interventions to avert kidney disease has grown en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 144 publications
0
5
0
Order By: Relevance
“…Investigation of the potential mechanisms underlying renal programming has gained increasing attention [ 9 , 60 ]. Currently, the mechanisms accounting for renal programming include deficient NO [ 116 ], oxidative stress [ 2 , 117 ], the aberrant renin–angiotensin–aldosterone system (RAAS) [ 118 ], and gut microbiota dysbiosis [ 119 , 120 ]. The results of animal experiments indicate that the H 2 S signaling pathway interacts with the abovementioned mechanisms.…”
Section: Mechanisms Behind Protective Actions Of H 2 ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Investigation of the potential mechanisms underlying renal programming has gained increasing attention [ 9 , 60 ]. Currently, the mechanisms accounting for renal programming include deficient NO [ 116 ], oxidative stress [ 2 , 117 ], the aberrant renin–angiotensin–aldosterone system (RAAS) [ 118 ], and gut microbiota dysbiosis [ 119 , 120 ]. The results of animal experiments indicate that the H 2 S signaling pathway interacts with the abovementioned mechanisms.…”
Section: Mechanisms Behind Protective Actions Of H 2 ...mentioning
confidence: 99%
“…Methionine and cysteine are precursors of glutathione, which play a prominent role in oxidative stress [ 1 ]. It is known that oxidative stress is involved in the development of kidney disease [ 2 ]. Homocysteine is a non-protein-bound sulfur amino acid implicated in one-carbon metabolism and kidney disease [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a well-known antioxidant, melatonin displays a protective role against oxidative stress by scavenging free-radicals and activating antioxidant enzymes [2]. A previous review revealed that several environmental stimuli in pregnancy linked oxidative stress to the developmental programming of kidney disease [85], covering maternal nutrition imbalance, maternal disorders, environmental chemical and toxin exposure, and medication use.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…The kidneys are prone to oxidative stress [ 45 ]. This biomarker was chosen because of its role as a scavenger of free radicals and thus has a role in oxidative-stress-related renal diseases in neonates [ 46 ].…”
Section: Introductionmentioning
confidence: 99%